Effects of two grading techniques of zirconia material on the fatigue limit of full-contour 3-unit fixed dental prostheses - Villefort, Regina Furbino [UNESP]; Amaral, Marina [UNESP]; Pereira, Gabriel Kalil Rocha; Campos, Tiago Moreira Bastos; Zhang, Yu; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe [UNESP]; de Melo, Renata Marques [UNESP] (Elsevier, 2017)
Objective This study evaluated the effects of two grading techniques of zirconia material on the fatigue limit of full-contour 3-unit fixed dental prostheses (FDPs). Methods Presintered blocks of 3Y-TZP were milled to obtain sixty-nine 3-unit FDPs, which were divided into three groups (n = 23). The control group (CTL) was sintered and glazed following manufacturer's instructions. In the two experimental groups presintered FDPs received a surface silica/glass infiltration treatment before the sintering process. Silica sol–gel group (SSG) was graded by the sol–gel processing route, while the glass-zirconia-glass group (GZG) was graded by an enameling technique. Graded groups did not receive a glaze layer after sintering. All FDPs were then luted with a dual-curing resin cement on composite abutments, embedded in polyurethane and stored in water for five days. The initial load of the fatigue test was calculated based on the results of the monotonic testing applied on three specimens of each group. To determine the fatigue limit, 20 samples of each group were subjected to staircase testing (100,000 cycles/5 Hz). Results The fatigue limits (in Newtons) were CTL = 1607.27, SSG = 1824.31, and GZG = 2006.57, and the Dixon and Mood test indicated statistically significant differences among groups (95% confidence interval) (GZG > SSG > CTL). Significance The infiltration of silica and glass on bulk zirconia, by two different grading methods, increased the fatigue limits of monolithic zirconia FDPs.
Keywords: Fatigue; Fixed dental prostheses; Mechanical; Silicon dioxide; Stress; Zirconium